SLIPS OF THE EAR EXPERIENCED BY INDONESIAN ELEMENTARY SCHOOL STUDENTS IN PERCEIVING NON-JAVANESE ACCENTED CHILDREN' SPEECH WITHIN QUIET SITUATION - Aliifah, Firly Nur; Syukri, Masitha Achmad (Department of Master of Linguistic, Universitas Airlangga, 2024)
Abstract: In psycholinguistics, slips of the ear involving the area of speech perception have accumulated data in recent years. Slip of the ear (SOE) is a phenomenon that occurs when someone misunderstands what the speaker has communicated, whether in quiet or busy environments. The objective of this current study is to identify and determine the many forms of ear slips as defined by Bond (2005), with a focus on the most commonly occurring varieties. The participants in the study were 40 elementary school pupils from grades 3, 4, and 5 at SDN 1 Gubeng Surabaya. These students did not have any hearing impairment and their first language was Bahasa Indonesia. The method used pre-experimental design by giving a listening task in which the voice of speakers used two different accents that were Dayak-Melayu and Minang. Hence, there were 10 sentences in which the participants had to complete the blank space in each sentence. There were 254 incorrect answers, classified into 11 types out of 14 types of SOE. Furthermore, the most frequent type of SOE found is well-formed and ill-formed utterances (30.77%). Lastly, it may be concluded that even in quiet situations and in their own first language, the participants still misperceived the utterance or the gap in every sentence. Keywords: elementary school students; quiet situation; slips of the ear; speech perception. Abstrak: Dalam psikolinguistik, keliru dengar melibatkan area persepsi ucapan telah tercatat dalam data dalam beberapa tahun terakhir. Fenomena slips of the ear terjadi karena kesalahpahaman seseorang terhadap apa yang telah disampaikan oleh pembicara baik dalam situasi hening maupun ramai. Tujuan dari penelitian ini adalah untuk mengetahui jenis dan tipe slips of the ear yang paling sering terjadi menurut Bond (2005). Terdapat 40 siswa SD kelas 3, 4, dan 5 SDN 1 Gubeng Surabaya sebagai peserta, tidak memiliki gangguan pendengaran, dan menggunakan bahasa Indonesia sebagai bahasa pertama mereka. Metode yang digunakan adalah pre-experimental design dengan memberikan tugas menyimak dimana suara pembicara menggunakan dua aksen yang berbeda yaitu Dayak-Melayu dan Minang, sehingga ada 10 kalimat yang harus diisi oleh peserta pada setiap kalimat. Studi ini menemukan ada 254 jawaban salah yang diklasifikasikan ke dalam 11 jenis dari 14 jenis slips of the ear. Selain itu, jenis slip of the ear yang paling banyak terjadi dalam penelitian ini adalah ujaran well-formed dan ill-formed senilai 30,77%. Akhirnya, dapat disimpulkan bahwa dalam situasi hening dan bahasa pertama mereka sendiri pun, para peserta masih mengalami salah mempersepsikan ucapan atau celah di setiap kalimat. Kata kunci: keliru dengar, persepsi ucapan; siswa SD; situasi hening.